What Constitutes an Effective English Teacher: Perceptions of Thai Tertiary Learners in Thailand - Waelateh, Bordin; Ambele, Eric A.; Boonsuk, Yusop; Wasoh, Fa-ezah (วารสารวิทยบริการ มหาวิทยาลัยสงขลานครินทร์ | Academic Services Journal, Prince of Songkla University; Vol 30 No 3 (2562): Academic Services Journal, Prince of Songkla UniversityDO - 10.14456/asj-psu.2019.58, 2019)
Globalization and superdiversity has brought about many studies in ELT institutions globally into what constitutes an effective English teacher in the 21st Century, but such works have been studied from the viewpoints of teachers, with little or no attention paid to this same phenomenon from the student’s point of view. Therefore, this paper examines the realistic change in views of who an effective English language teacher is as perceived by Thai tertiary learners in Thailand. The study further accounts for why this issue is a prevailing reality in this context. A questionnaire survey sampling method was employed to collect data constituting 16 undergraduate tertiary learners of English major in Thailand, prior to the utilization of a semi-structured interview. The data analysis was content-based on the initial, semi-structured questionnaire of 100 students. The findings showed that the learners de-emphasized nationality, place of birth, physical appearance and first language as relevant constituents of effective English teachers as these are not representative of their (in)ability to teach English. For them, a professional or unqualified English teacher should be measured through robust and practical characteristics: personal characteristics, pedagogical characteristics, cultural sensitivity, linguistic characteristics, and Professional characteristics. These have practical implications for the recruitment and employment of teachers in Thailand as English teachers. Keywords: tertiary learners’ voices, effective English teacher, Thai context